The use of translation as a learning method for the German language students in University Putra Malaysia - Bong, Tze Ying; Ang, Lay Hoon; Ogasa, Nicole; Abdul Halim, Hazlina; Majtanova, Miroslava (2015)
Based on the growing numbers of research studies, the use of translation in learning foreign language has shown that this topic is getting more popular to the public and education research group. The researchers have investigated a large number of methods that are being employed in foreign language learning, but the method of translation has still been an issue that creates lots of controversy. It is a challenging task for a non-native speaker to learn a foreign language especially if the grammar of the students’ dominant language is different from the foreign language. This study is primarily designed to understand the role of translation for non-native speakers when learning German as a foreign language. The objectives of this study are to ascertain the students’ beliefs about using translation in their studies, and to find out the language learning skills of which translation strategy is widely used. A total of 30 undergraduates studying German as a foreign language in University Putra Malaysia have participated in this study. Data collection was made by using questionnaire. With reference to the findings of the study, it can be concluded that the majority believes that the use of translation is a helping strategy in the learning of the German language. Although a small numbers of students preferred to learn German language without using translation, they also agreed that translation did really help to develop their learning strategy in a situation where they do not understand the lecturer use German language to teach in class. Besides, the findings also showed the student used a wide variety of learning strategies which involved translation in different learning skills. The findings of this study can support to the schools and instructors in developing a better German language learning program.